Is primary production in holm oak forests nutrient limited? (Plant Ecology, 1992)
Correlations between primary production and patterns of nutrient use and nutrient availability were investigated in 18 plots in closed holm oak (Quercus ilex L.) stands in the Montseny mountains (NE Spain), searching for evidence of nutrient limitation on primary production. The plots spanned a range of altitudes and slope aspects within a catchment. Nutrients considered were nitrogen (N), phospho- rus (P), potassium (K) and magnesium (Mg) in plant samples, and the above plus calcium (Ca) and sodium (Na) in the soil. Primary production was found by summing the annual aboveground biomass increment to the annual litterfall. Across plots, primary production was correlated with the annual re- turn of nutrients in litterfall, but this relationship probably arose from the common effects of the amount of litterfall on both primary production and nutrient return, and not from any nutrient limitation. Pri- mary production was not significantly correlated with nutrient concentrations in mature leaves nor leaf litterfall, nor with absolute or relative foliar retranslocation of nutrients before leaf abscission, nor with the concentration and content (kg/ha) of total N, extractable P, and exchangeable K, Mg, Ca and Na in the upper mineral soil. We conclude that there is no correlational evidence that primary production is nutrient limited in this holm oak forest.